Risk Assessment for Long-term Injury of Oil Palm Harvester - Arief RM Akbar; Alan Dwi Wibowo; Bima Hairul Asyikin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Fresh fruit bunches (FFB) are mostly harvested manually in large and small plantations. Ergonomically, this type of work has the potential to cause permanent muscle injuries over time. Based on these concerns, a study was conducted to assess the workload by monitoring heart rates using a Heart Rate Monitor for each task element of the oil palm fruit harvesters. The risk level of these harvesters was also assessed using the Rapid Entire Body Assessment (REBA) method. The risk levels were evaluated based on the weight and height of harvesters. The analysis of the harvesters' workload, based on heart rate measurements during different harvesting activities, shows that cutting bunches and fronds falls into the heavy workload category. Moving between locations is classified as a moderately heavy workload, while unloading and organizing bunches at the collection site (TPH) is considered a light workload. The results of the risk level analysis for the harvesters show that for the minimum weight variable, the risk is in the moderate risk category, while for the maximum weight variable, the risk is classified as high. In terms of height, both the minimum and maximum height variables fall into the moderate risk category. Keywords: Ergonomics, Oil palm harvesters, Rapid entire body assessment, Risk level, Workload.